Make or buy in the hotel marketing department: transaction costs, financial and relational performance - Tomás F. Espino-Rodríguez; Manuel Rodríguez Díaz (Tourism & Management Studies)
The outsourcing of hotel marketing is one of the strategic decisions that can help hotels manage the distribution channels more efficiently. This study analyzes the factors determining the outsourcing of hotel sales and marketing activities. It uses the transaction costs framework, complemented by the analysis of performance costs and quality. In this context, the possible impact of outsourcing the marketing department on relational and financial performance is analyzed. The results of the study clearly show a close relationship between these variables and current outsourcing. In addition, the increase in outsourcing is determined by low relational quality. These results lead to the conclusion that it is necessary to create new systems and procedures in sales and ma